Prevalence of caries on panoramic radiographs at Radiology Installation RSGMP Hasanuddin University Makassar in 2022 after Covid-19 pandemic: Prevalensi karies pada radiografi panoramik di Instalasi Radiologi RSGMP Universitas Hasanuddin Makassar tahun 2022 pasca pandemi Covid-19 - Barunawaty Yunus; Raditya Nasrullah Azhar (Makassar Dental Journal, 2023)
The Covid-19 pandemic has triggered various sectors to experience disruption, one of which is the oral health service sector. This study was conducted to determine the prevalence of dental caries cases found in the Radiology Installation of RSGMP Hasanuddin University after the Covid-19 pandemic. Descriptive observational study was conducted through panoramic and periapical radiographic data from March-September 2022, then the results were entered into distribution tables and graphs. From the periapical radiographic examination, it was found that the most caries were in women (61.7%). Based on age, most of them occurred in the adolescent group at 44.6%, 10.6% of men and 19.1% of women had Class I caries, 25.5% of men and 29.7% of women had Class II caries, 2.1% of men and 6.3% of women had Class III caries. No men and 4.2% of women had Class IV caries, no men and 2.1% of women had Class V caries. It is concluded that the prevalence of caries is most prevalent in women and the majority is class II.